Microstructure and Mechanical Properties of Pack Carburized AISI 1020 Steel Using Na2CO3 and CaCO3 Catalysts - Abdul Karim; Ilham Azmy; Silviani Qotrunnida Khoiriah; Carolus Bintoro (Journal of Renewable Energy and Mechanics, 2022)
AISI 1020 steel is categorized in low carbon steel which widely used for automotive parts industry and construction because its characteristic like high ductility, relatively low hardness value, and high formability. In continuously usage for long time, this steel tends to be worn down because its low surface hardness value. The surface hardness is congruity to wear resistance of AISI 1020 steel. In this research, the experimental method of pack carburizing process was carried out by heating AISI 1020 steel samples packed along charcoal with catalysts variation of Na2CO3 and CaCO3 till temperature 900 oC and hold it for 4 hours to effect diffusion carbon mechanism in surface treatment. Thereupon, AISI 1020 steel samples was fast cooled by using distilled water. The selection of different catalyst variation according to diffusion capability which will be expected to enhance AISI 1020 steel’s microstructure and mechanical properties. From this research, it obtained that pack carburized AISI 1020 steel using Na2CO3 possesses significant microstructure transformation which will affect to the highest hardness value increment (505,4 HV) and the lowest wear rate decrease (0,00821 mm3/minute). Thereby, pack carburized AISI 1020 steel using Na2CO3 also exhibits good wear resistance characteristic so that can be used in long lifetime.